Calculations with spectroscopic accuracy: Energies and transition parameters for lines of fusion interest in Mo XXXIX. (December 2018) - Chen, Zhan-Bin; Wang, Kai
Highlights: Excitation energies, transition wavelengths, and transition probabilities for lines of fusion interest in Mo XXXIX are reported. Two sets of atomic parameters, independently calculated, excellently agreed with each other, suggesting that there is a high degree of convergence achieved in this study. The most accurate and complete, as of today, atomic data for Mo XXXIX are provided. The present data particularly important for fusion research. Abstract: We have performed high-accuracy calculations of energy levels, wavelengths, lifetimes, line strengths and radiative rates among the 250 lowest levels of the (1 s 2 )2 s 2, (1 s 2 )2 s 2 p, (1 s 2 )2 p 2, (1 s 2 )2 snl ( n =3, 4, 5, 6; l =0, 1, 2, 3, 4, 5), and (1 s 2 )2 pnl ( n =3, 4, 5, 6; l =0, 1, 2, 3, 4, 5) configurations of Mo XXXIX. The second-order relativistic many-body perturbation theory (MBPT) is adopted and data are provided for all electric/magnetic-dipole (E1/M1) and electric/magnetic-quadrupole (E2/M2) transitions. Similar data for the 98 lowest levels of the n  ≤ 4 configurations are also determined using fully relativistic multi-configuration Dirac-Fock (MCDF) wave functions in the active space approximation with the inclusion of a finite nuclear size, the Breit interaction, self-energy, and vacuum polarization to assess the accuracy of the calculations. Based on direct comparisons between the results obtained from these two independent methods, MBPT and MCDF, as well as with the other available theoretical values and measurements, our energies are assessed to be accurate to better than 0.02%. The accuracy for strong radiative rates is estimated to be about 5%. For Mo XXXIX, only a few transition lines have been established experimentally. The present new results considerably expand the existing data sets for this ion, and should be beneficial in analysis of experimental spectra and useful for spectroscopic diagnostics and modeling of hot plasmas, in particular in fusion devices.